A new species of blind skink (Squamata: Dibamidae: Dibamus) from Chu Yang Sin National Park, southern Vietnam, with the first description of a Dibamus clutch - Kliukin, Nikita S.; Bragin, Andrey M.; Nguyen, Tan Van; Vu, Duy Dinh; Le, Son Xuan; Gorin, Vladislav A.; Krone, Isaac W.; Poyarkov, Nikolay A. (Zootaxa, 2026)
A new species of dibamid lizard, Dibamus irregularis sp. nov. is described based on molecular (three mitochondrial genes) and morphological (external and skeletal) characters of twelve specimens collected from the Chu Yang Sin National Park, Dak Lak Province, southern Vietnam. The new species can be distinguished from other congeners by the following combination of characters: medial rostral suture absent or incomplete, nasal sutures incomplete, labial sutures complete or incomplete; two to three postoculars; three to four scales on the posterior edge of infralabial; 22–24 midbody scale rows; 180–211 ventral scales; 39–46 subcaudal scales; and maximum snout-vent length 147 mm. Moreover, two eggs of a new species were collected in the same locality. The only known clutch of Dibamus was described more than 120 years ago based on a single egg of D. alfredi collected from Bukit Besar, Thailand. Herein, we provide the first description of a complete clutch of the genus Dibamus based on two eggs of Dibamus irregularis sp. nov. Our study brings the total number of species in the genus Dibamus to 30; Dibamus irregularis sp. nov. is the 10th species of Dibamus recorded from Vietnam, highlighting the importance of the country as a hot spot of reptilian diversity in Southeast Asia.